Therapeutic potentials of n-hexane extracts of the three medicinal mushrooms regarding their anti-colon cancer, antioxidant, and hypocholesterolemic capabilities - ghoson Daba; Waill Elkhateeb; Asmaa Negm ELDien; Eman Fadl; Ali Elhagrasi; Walid Fayad; Ting Chi Wen (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Daba GM, Elkhateeb WA, El-Dien AN, Ahmed EF, El Hagrassi AM Fayad W, Wen TC. 2020. Therapeutic potentials of n-hexane extracts of the three medicinal mushrooms regarding their anti-colon cancer, antioxidant, and hypocholesterolemic capabilities. Biodiversitas 21: 2437-2445. Evaluating in vitro biological activities of the medicinal mushrooms Hericium erinaceus, Metacordyceps neogunnii, and Dictyophora indusiata n-hexane extracts revealed their capabilities as promising therapeutic sources. By assessing their DPPH radical scavenging activities, D. indusiata extract exhibited the highest antioxidant activity (87.8±1.2%) followed by H. erinaceus, then M. neogunnii 84.9±1.6%, and 77.3±1.3%, respectively. On the other hand, M. neogunnii extract exerted promising anti-colon cancer (68.6±3.6% cytotoxicity) against HCT116 human colon cancer cell lines at concentration 100 ?g/mL, whereas H. erinaceus and D. indusiata extracts exhibited weaker cytotoxic effects (18.3±1.7%, and 19.3±3.2%, respectively) using the same concentration. Investigating cholesterol reduction activities (CRA%) of the extracts revealed that activity depends on both extract concentration and incubation period. After 96 h of incubation at room temperature, all extracts exerted potent in vitro hypocholesterolemic activities (100±0% reduction in cholesterol concentration). Performing GC-Ms analyses on the extracts revealed presence of 22 compounds in D. indusiata extract, while 29 compounds were detected in M. neogunnii extract, and 33 in H. erinaceus extract. Most of compounds were esters of fatty acids. Results in this study encourage using these mushrooms as functional foods, and highlight the need for conducting further in vivo studies to support their use in pharmaceutical industry.